Electrode precursor material and preparation method thereof, preparation method of positive electrode material, positive electrode plate and secondary battery

By adopting electrode precursor material with egg yolk shell structure, the stability problems caused by structural changes in metal oxide electrode materials during circulation are solved, and high reversible capacity, good rate performance and cycling performance are achieved.

CN119461505APending Publication Date: 2025-02-18HUAYOU NEW ENERGY TECH (QUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580967.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18

Smart Images

  • Figure CN119461505A_ABST
    Figure CN119461505A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode precursor material and a preparation method thereof, a preparation method of a positive electrode material, a positive electrode plate and a secondary battery. The structure of the electrode precursor material comprises a surface layer shell and a metal oxide core from outside to inside, the surface layer shell comprises a metal oxide shell layer and a tin oxide coating layer, a hollow cavity is formed between the surface layer shell and the metal oxide core, and the surface layer shell has a microporous structure. The material has a yolk shell structure, so that a large contact area between an electrode and an electrolyte is ensured, and the reversible capacity can be remarkably improved. Open pores distributed on the surface of the shell enhance the permeation of the electrolyte, shorten the diffusion length of sodium or lithium ions, and improve the rate performance. The void space of the layered yolk shell structure provides a buffer area for huge volume expansion caused by insertion / extraction of sodium or lithium ions, and the structural stability is improved. By doping Sn < 2 + >, phase change during circulation can be inhibited, and the electrochemical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to an electrode precursor material and a preparation method thereof, a preparation method of a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Metal oxides have rich valence electron configurations, simple preparation methods, strong electrochemical reversibility, high specific capacitance and other excellent properties, and are widely used in electrode materials. For example, layered transition metal oxides, as advanced positive electrode materials for sodium ion batteries, have received widespread attention in recent years due to their large theoretical capacity, excellent rate performance, and long cycle life. At present, metal oxide materials used as electrode materials generally still have some problems due to their own structure and characteristics. For example, structural changes are prone to occur during the charge and discharge cycle, resulting in capacity loss of electrode materials, and volume expansion caused by the insertion and extraction of single positively charged ions, which leads to poor chemical and electrochemical stability of metal oxides and affects cycle performance. Therefore, the performance of metal oxide electrode materials needs to be improved.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide an electrode precursor material and a preparation method thereof, as well as a preparation method of a positive electrode material, a positive electrode sheet and a secondary battery, so as to improve the above technical problems.

[0005] The present invention is achieved in that:

[0006] In the first aspect, the present invention provides an electrode precursor material, whose structure includes a surface shell and a metal oxide core from the outside to the inside, the surface shell includes a metal oxide shell layer and a tin oxide coating layer coated on the surface of the metal oxide shell layer, wherein there is a hollow cavity between the metal oxide shell layer and the metal oxide core, and the surface shell has a microporous structure connecting its outer surface and the hollow cavity.

[0007] Optionally, the metal oxide constituting the metal oxide core and the metal oxide shell are the same, and the metal element of the metal oxide of the electrode precursor material is selected from at least one of Ni, Co, Mn, Cu, Mg, Mo, W, Ca, Zn, Nb, Cr, Zr, Ti and Fe.

[0008] Optionally, the metal elements of the above metal oxide are Ni x A y Mn 1-x-y , wherein A is selected from at least one of Co, Fe and Cu, 0.9≥x>0.5, 0.5≥y>0.1.

[0009] Optionally, the metal elements of the metal oxide are stoichiometrically Ni x Fe y Mn 1-x-y , where 0.9≥x>0.5, 0.5≥y>0.1; the unit cell parameters of battery precursor materials have the following characteristics: α=β=γ=90°. In the X-ray diffraction pattern, the ratio of the diffraction peak intensity of the (311) crystal plane to the diffraction peak intensity of the (440) crystal plane is 2.6~2.9.

[0010] Optionally, the particle size of the metal oxide core is 50 nm to 500 nm, the thickness of the metal oxide shell is 1 nm to 10 nm, and the thickness of the tin oxide coating layer is 0.5 nm to 2 nm;

[0011] Optionally, the micropore size of the microporous structure is 0.1 nm to 20 nm, and the specific surface area of ​​the battery precursor material is 4 to 10 m 2 / g.

[0012] In a second aspect, the present invention further provides a method for preparing the above electrode precursor material, which comprises:

[0013] The metal salt solution and the tin chloride solution are respectively sprayed into a pyrolysis furnace through two atomizing nozzles, and pyrolyzed in an oxygen atmosphere to form an electrode precursor material, wherein a template agent is added to the metal salt solution.

[0014] Optionally, the template is selected from at least one of polyvinyl pyrrolidone (PVP), polyamide-amine (PAMAM), polyacrylamide (PAM), citric acid (CA), polyvinyl alcohol (PVE) and ethylenediamine (EDA); preferably, the template is polyvinyl pyrrolidone.

[0015] Optionally, the pyrolysis temperature is 600°C to 1000°C, preferably 700°C to 900°C.

[0016] Optionally, the negative pressure value of the electrode precursor material pyrolysis furnace is -100Pa to -500Pa.

[0017] Optionally, the amount of template added to the metal salt solution is 0.5 g / L to 5 g / L, preferably 3 g / L to 5 g / L;

[0018] Optionally, the total metal ion concentration in the metal salt solution is 100 g / L to 250 g / L, preferably 150 g / L to 200 g / L;

[0019] Optionally, the concentration of the tin chloride solution is 0.1 mol / L to 2 mol / L, preferably 0.5 mol / L to 1 mol / L;

[0020] Optionally, the ratio of the inlet flow rate of the metal salt solution to the inlet flow rate of the tin chloride solution is (1-5):1, preferably (2-4):1.

[0021] In a third aspect, the present invention further provides a method for preparing a positive electrode material, which comprises: sintering the above-mentioned electrode precursor material with a sodium source or a lithium source.

[0022] In a fourth aspect, the present invention further provides a positive electrode plate, which includes a current collector and a positive electrode film layer disposed on the current collector, wherein the positive electrode film layer comprises the positive electrode material prepared by the above preparation method.

[0023] In a fifth aspect, the present invention further provides a secondary battery comprising the above-mentioned positive electrode plate.

[0024] The present invention has the following beneficial effects: through the yolk shell structure composed of the surface shell and the metal oxide core, and the surface shell has a microporous structure that penetrates the inside and outside, so that the positive electrode material obtained by further sintering the electrode precursor material with the sodium source or lithium source, its functional surface shell and the metal oxide core can contact the electrolyte, ensuring a large contact area between the electrode and the electrolyte, thereby providing more active sites for ions with a single positive charge, so as to significantly improve the reversible capacity; at the same time, the microporous structure distributed in the surface shell not only provides a large interface for the storage of ions with a single positive charge (such as sodium ions), but also enhances the penetration of the electrolyte, shortens the diffusion length of lithium ions, and can improve the rate performance. And the void space provided by the hollow cavity located in the surface shell and the metal oxide core provides a buffer area for the huge volume expansion caused by the insertion / extraction of lithium ions, thereby improving the stability of the structure and improving the cycle performance. In addition, the incorporation of tin ions in the tin oxide coating of the surface shell helps phase change during cycling, improves electrochemical performance, reduces cation mixing in the positive electrode material, and inhibits undesirable side reactions at the electrolyte interface caused by the high alkalinity of the active material surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 Schematic diagram of the structure of an electrode precursor material according to an embodiment of the present invention;

[0027] Figure 2 This is the X-ray diffraction pattern of the electrode precursor material of Example 1 of the present invention.

[0028] Icon: 100-tin oxide coating; 200-metal oxide shell; 300-hollow cavity; 400-metal oxide core. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0030] The following is a detailed description of an electrode precursor material and a preparation method thereof, as well as a preparation method of a positive electrode material, a positive electrode sheet and a secondary battery provided by the present invention.

[0031] join Figure 1 Some embodiments of the present invention provide an electrode precursor material, whose structure includes a surface shell and a metal oxide core 400 from the outside to the inside, wherein the surface shell includes a metal oxide shell layer 200 and a tin oxide coating layer 100 coated on the surface of the metal oxide shell layer, wherein a hollow cavity 300 is provided between the metal oxide shell layer 200 and the metal oxide core 400, and the surface shell has a microporous structure connecting its outer surface and the hollow cavity.

[0032] The embodiment of the present invention proposes that the precursor oxide structure includes a yolk-shell structure, surface pores and a tin oxide coating layer. The yolk-shell structure provides a buffer space for the volume change during the ion deintercalation process of the positive electrode material, improves the structural stability of the positive electrode material, provides a fast ion / electron transport channel, strengthens the adsorption of intermediate products and improves the conversion reaction efficiency, etc., and provides the positive electrode material with high reversible capacity, good rate performance and cycle performance; the surface pores can alleviate the volume change during the ion deintercalation process, serve as an ion migration channel, and at the same time increase the specific surface area, enhance the reaction activity, and improve the conductivity; the tin oxide coating layer reduces Ni 2+ The generation of lattice oxygen can be effectively inhibited, thereby improving the material's cycle and rate performance, while reducing the contact between active substances and electrolytes, thereby improving the material's cycle performance.

[0033] It should be noted that there is a hollow cavity 300 and a small amount of fine particles (metal oxide formed after pyrolysis) between the metal oxide shell 200 and the metal oxide core 400. In addition, it should be noted that the metal oxide core 400 is composed of spheres with densely distributed particles.

[0034] Specifically, in some embodiments, the particle size of the metal oxide core 400 is 50nm to 500nm. For example, the particle size of the metal oxide core 400 can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc., or any value between any two point values; the thickness of the metal oxide shell 200 is 1nm to 10nm. For example, the metal oxide The thickness of the shell 200 may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, or any value between any two point values; the thickness of the tin oxide coating layer 100 is 0.5 nm to 2 nm. For example, the thickness of the tin oxide coating layer 100 may be 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.5 nm, 1.8 nm or 2 nm, etc., or any value between any two point values.

[0035] The size selection of the metal oxide core 400, the metal oxide shell 200 and the tin oxide coating 100 is conducive to better contact between the electrode material and the electrolyte, and is more convenient for the insertion or removal of sodium ions or lithium ions. At the same time, the thickness selection of the tin oxide can, on the one hand, help to inhibit the phase change during the cycle and the undesirable side reaction at the electrolyte interface due to the high alkalinity of the active material surface, and on the other hand, it can reduce the cation mixing of the positive electrode material. At the same time, the tin oxide will not have a significant impact on the electrochemical performance due to its excessive thickness.

[0036] In some embodiments, the micropore size of the microporous structure is 0.1nm to 20nm. It should be noted that the micropores here are naturally generated during the pyrolysis reaction and vary in size, but their particle sizes are distributed in the range of 0.1nm to 20nm. Further, under the premise of having the above-mentioned micropore size, the specific surface area of ​​the battery precursor material is 4 to 10m 2 / g. The appropriate micropore size and a large number of micropores provide a large interface for the storage of sodium or lithium ions, and are conducive to the penetration of electrolytes, which can effectively shorten the diffusion length of lithium ions and improve the rate performance.

[0037] In some embodiments, based on the metal element composition corresponding to different metal oxides, the above-mentioned electrode precursor material can be an electrode precursor material for a sodium ion battery or an electrode precursor material for a lithium ion battery. Specifically, in general, the metal oxides constituting the metal oxide core and the metal oxide shell are the same, and the metal element of the metal oxide of the electrode precursor material is selected from at least one of Ni, Co, Mn, Cu, Mg, Mo, W, Ca, Zn, Nb, Cr, Zr, Ti and Fe.

[0038] Furthermore, in some embodiments, the metal elements of the metal oxide are stoichiometrically composed of Ni x A y Mn 1-x-y , wherein A is selected from at least one of Co, Fe and Cu, 0.9≥x>0.5, 0.5≥y>0.1, for example, the value of x can be 0.6, 0.7, 0.8, 0.9, etc., and the value of y can be 0.4, 0.3, 0.2, 0.1, etc.

[0039] Furthermore, in some embodiments, the electrode precursor material is a positive electrode precursor material for a sodium ion battery, that is, the metal oxide is a transition metal oxide, and the metal element is Ni in a stoichiometric ratio. x Fe y Mn 1-x-y , where 0.9≥x>0.5, 0.5≥y>0.1, for example, the value of x can be 0.6, 0.7, 0.8, 0.9, etc., and the value of y can be 0.4, 0.3, 0.2, 0.1, etc. And the unit cell parameters of the battery precursor material have the following characteristics: α=β=γ=90°. In the X-ray diffraction pattern, the ratio of the diffraction peak intensity of the (311) crystal plane to the diffraction peak intensity of the (440) crystal plane is 2.6~2.9.

[0040] Furthermore, some embodiments of the present invention also provide a method for preparing the above-mentioned electrode precursor material, which comprises: spraying a metal salt solution and a tin chloride solution into a pyrolysis furnace respectively through two atomizing nozzles, and pyrolyzing them in an oxygen atmosphere to form an electrode precursor material, wherein a template is added to the metal salt solution.

[0041] At present, the yolk-shell structure material is mainly synthesized by hydrothermal method and coprecipitation method, and these methods generally have complex reaction conditions, long reaction time and cumbersome reaction steps. The above embodiment of the present invention adopts spray pyrolysis technology, and realizes the preparation of electrode precursor material of yolk-shell structure in one step. Specifically, in the spray pyrolysis process, the metal salt solution is atomized into tiny droplets by an atomizing nozzle, and then these tiny droplets are pyrolyzed under high temperature conditions. In this process, the metal ions in the droplets will undergo oxidation reaction with oxygen to form crystal nuclei of metal oxides, and then continue to grow at high temperature to form metal oxide particles. At the same time, the template agent will undergo secondary combustion in an oxygen atmosphere, so that part of the metal oxide wraps the metal oxide particles in the form of an outer shell, and the gas generated by the combustion of the template agent will also cause a large number of micropores in the outer shell to penetrate the outer shell. In addition, the inventors have creatively utilized the property of tin chloride that rapidly vaporizes at high temperatures. When a tin chloride solution is introduced at the same time as a metal salt solution, the tin chloride reacts in the form of gas on the surface of the outer shell of the metal oxide to form a tin oxide coating layer. The gas generated by the combustion of the internal template will also make the tin oxide coating layer have micropores.

[0042] Specifically, in some embodiments, the template agent is selected from at least one of polyvinyl pyrrolidone, polyamide-amine, polyacrylamide, citric acid, polyvinyl alcohol and ethylenediamine. Exemplarily, the template agent can be selected as polyvinyl pyrrolidone. In addition to playing the role of template in the above reaction mechanism, polyvinyl pyrrolidone can also disperse the solution, prevent particle agglomeration and assist in pyrolysis.

[0043] In some embodiments, the metal salt solution includes any one or more aqueous solutions of chlorides, sulfates, nitrates, and oxalates.

[0044] In some embodiments, the amount of the template added in the metal salt solution is 0.5g / L to 5g / L, such as 0.5g / L, 1g / L, 1.5g / L, 2g / L, 2.5g / L, 3g / L, 3.5g / L, 4g / L, 4.5g / L, 5g / L, etc., or any value between the above two point values, preferably 3g / L to 5g / L. If the amount of the template added is too small, it is not easy to form a hollow cavity between the metal oxide core and the metal oxide shell, and a large number of micropores cannot be formed on the metal oxide shell and the tin oxide coating. If the amount of the template added is too large, it is easy to affect the formation of the yolk shell structure, and it is not conducive to the formation of the tin oxide coating. It should be noted that after the template is burned during the pyrolysis process, carbon will remain in the hollow cavity 300, which has a certain conductivity and will not affect the performance of the precursor material. The range of carbon residue is 0.005wt% to 0.05wt%.

[0045] In some embodiments, the total metal ion concentration in the metal salt solution is 100 g / L to 250 g / L, such as 100 g / L, 120 g / L, 140 g / L, 160 g / L, 180 g / L, 200 g / L, 220 g / L, 240 g / L, 250 g / L, etc., or any value between the above two points, preferably 150 g / L to 200 g / L. The total metal ion concentration in the above range is conducive to the atomization of the metal salt solution and the nucleation and growth of the metal oxide.

[0046] In some embodiments, the concentration of the tin chloride solution is 0.1mol / L to 2mol / L, 0.1mol / L to 2mol / L, such as 0.1mol / L, 0.3mol / L, 0.5mol / L, 0.7mol / L, 0.9mol / L, 1.2mol / L, 1.5mol / L, 2mol / L, etc., or any value between the above two point values, preferably 0.5mol / L to 1mol / L. Further, the ratio of the inlet flow rate of the metal salt solution to the inlet flow rate of the tin chloride solution is (1 to 5): 1, such as 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, 4: 1, 5: 1, etc., or any value between the above two point values, preferably (2 to 4): 1.

[0047] It should be noted that the concentration of the tin chloride solution and the inlet ratio to the metal salt solution will affect the thickness of the tin oxide coating layer, and will also affect the thermal decomposition reaction effect of the eggshell layer structure.

[0048] Furthermore, in order to generate a specific yolk-shell structure material by spray pyrolysis, and the morphology is uniform and the performance is stable, in some embodiments, the pyrolysis temperature is 600°C to 1000°C, such as 600°C, 700°C, 800°C, 900°C, 1000°C, or any value between the above two points, preferably 700°C to 900°C. Below this temperature range, the metal salt cannot be fully pyrolyzed, so that part of the metal oxide is directly coated on the surface of the metal oxide core, and the coating cannot be complete and uniform. In addition, the template agent cannot be pyrolyzed quickly, and thus the metal oxide shell layer with a porous structure and a hollow cavity between the metal oxide core cannot be formed by the rapid pyrolysis of the template agent; in addition, SnCl 4 The gasification and pyrolysis rates are reduced, and the precursor oxide particles cannot be fully and evenly coated. If the temperature is higher than this range, SnCl 4 If the gasification is too fast, the precursor oxide particles cannot be coated. If the metal salt is pyrolyzed too fast, the metal oxide shell cannot be formed, thereby affecting the formation of the yolk-shell structure with a hollow cavity. It should be noted that the pyrolysis temperature here refers to the average temperature after the pyrolysis furnace reaches a steady state.

[0049] In some embodiments, the negative pressure value of the electrode precursor material pyrolysis furnace is -100Pa to -500Pa, such as -100Pa, -150Pa, -200Pa, -250Pa, -300Pa, -350Pa, -400Pa, -450Pa, -500Pa, etc. The negative pressure is the negative pressure value of the pyrolysis furnace top, and the negative pressure is realized by exhaust gas blower to draw air outward. Too high negative pressure may cause tin oxide to fail to completely cover the precursor oxide. Appropriate negative pressure helps the reaction process to form particles with uniform morphology, and also helps the stability of the entire pyrolysis system.

[0050] Some embodiments of the present invention also provide a method for preparing a positive electrode material, which comprises: sintering the above electrode precursor material with a sodium source or a lithium source. The positive electrode material formed by sintering can retain the yolk-shell structure of the electrode precursor material, thereby having better electrochemical performance.

[0051] Some embodiments of the present invention further provide a positive electrode plate, which includes a current collector and a positive electrode film layer disposed on the current collector, and the positive electrode film layer includes the positive electrode material prepared by the above preparation method.

[0052] Some embodiments of the present invention further provide a secondary battery comprising the above-mentioned positive electrode plate.

[0053] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0054] Example 1

[0055] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0056] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0057] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0058] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0059] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 3:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 800°C.

[0060] (5) An electrode precursor material is obtained at the outlet of the pyrolysis furnace, and the electrode precursor material is analyzed by X-ray diffraction. The X-ray diffraction pattern is as follows: Figure 2 The obtained electrode precursor material is sintered to prepare a positive electrode for electrical performance testing. The specific steps of preparing the positive electrode material and the positive electrode sheet include:

[0061] (1) Weighing sodium carbonate and precursor oxide, mixing them evenly, and sintering them in a muffle furnace at 950° C. for 15 h to obtain a positive electrode material;

[0062] (2) Weigh the positive electrode material, the positive electrode conductive agent acetylene black and the positive electrode binder polytetrafluoroethylene, add them to the positive electrode solvent N-methylpyrrolidone and mix them evenly to obtain a positive electrode slurry, wherein the ratio of the positive electrode material, the conductive agent, the binder and the positive electrode solvent is 8:1:1:40; and evenly coat the positive electrode slurry on the surface of the positive electrode current collector to obtain a positive electrode.

[0063] The specific steps for preparing sodium ion batteries include:

[0064] (1) Preparing a negative electrode: Weighing a negative electrode active material, a negative electrode conductive agent acetylene black, and a negative electrode binder polytetrafluoroethylene, adding them to a negative electrode solvent N-methylpyrrolidone and mixing them evenly to obtain a negative electrode slurry, wherein the ratio of the negative electrode material, the conductive agent, the binder, and the negative electrode solvent is 8:1:1:40; uniformly coating the negative electrode slurry on the surface of the negative electrode current collector to obtain a negative electrode.

[0065] (2) preparing an electrolyte: adding sodium salt, ethylene carbonate (EC) and dimethyl carbonate (DMC) into an electrolyte solution and mixing them evenly to obtain an electrolyte, wherein the electrolyte is 1 mol / L NaPF6 / EC-DMC (volume ratio 1:1);

[0066] (3) Preparation of diaphragm: Cut the diaphragm Cellgard into required size;

[0067] (4) Assembling the positive electrode, the negative electrode, the separator and the electrolyte to obtain a sodium ion battery.

[0068] The performance test conditions are: the sodium ion battery is tested for the first cycle of charge and discharge activation at a current density of 0.1C to test the first week of charge and discharge capacity, and then tested for 100 cycles at a current density of 0.1C. The test results are: the first week of charge and discharge capacity reaches 149mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate is 97%.

[0069] Example 2

[0070] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0071] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 3:2:1 to prepare a metal salt solution. The total metal ion concentration of the prepared metal solution is 180 g / L.

[0072] (2) Add PVP at 4 g / L to the above metal salt solution and mix well.

[0073] (3) Prepare SnCl with a concentration of 0.7 mol / L 4 Solution.

[0074] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 2:1, the negative pressure was set at -200Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 900°C.

[0075] (5) Obtain electrode precursor material at the outlet of the pyrolysis furnace. Sinter the obtained electrode precursor material to prepare a positive electrode for electrical performance testing. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 152 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate is 96%.

[0076] Example 3

[0077] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0078] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 5:3:2 to prepare a metal salt solution. The total metal ion concentration of the prepared metal solution is 200 g / L.

[0079] (2) Add 5 g / L of PVP to the above metal salt solution and mix well.

[0080] (3) Prepare SnCl with a concentration of 1.0 mol / L 4 Solution.

[0081] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 4:1, the negative pressure was set at -300Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 1000°C.

[0082] (5) Obtain electrode precursor material at the outlet of the pyrolysis furnace. Sinter the obtained electrode precursor material to prepare a positive electrode for electrical performance testing. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 145 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 94.5%.

[0083] Example 4

[0084] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0085] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0086] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0087] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0088] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 1:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 800°C.

[0089] The difference between this embodiment and embodiment 1 is that the metal salt solution inlet flow rate is set to SnCl 4 The solution inlet flow rate is set at 1:1.

[0090] The obtained electrode precursor material was sintered to prepare a positive electrode for electrical performance testing. The electrode precursor material was prepared into a sodium ion battery and the test method was consistent with Example 1. The test results were: the charge and discharge capacity in the first week reached 140 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 92.9%.

[0091] Example 5

[0092] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0093] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0094] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0095] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0096] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate and the SnCl4 solution inlet flow rate are set at 5:1, the negative pressure is set to -100 Pa, and the pyrolysis temperature of the pyrolysis furnace is set to 800°C.

[0097] The difference between this embodiment and embodiment 1 is that the metal salt solution inlet flow rate is set to SnCl 4 The solution inlet flow rate is set at 5:1.

[0098] (5) The obtained electrode precursor material was sintered to prepare a positive electrode for electrical performance testing. The electrode precursor material was prepared into a sodium ion battery and the test method was consistent with Example 1. The test results were: the charge and discharge capacity in the first week reached 143.5 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 95.2%.

[0099] Example 6

[0100] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0101] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0102] (2) Add 0.5 g / L of PVP to the above metal salt solution and mix well.

[0103] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0104] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 3:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 800°C.

[0105] The only difference between this embodiment and embodiment 1 is that, in step (2), 0.5 g / L of PVP is added to the above metal salt solution and mixed evenly.

[0106] (5) The obtained electrode precursor material was sintered to prepare a positive electrode for electrical performance testing. The electrode precursor material was prepared into a sodium ion battery and the test method was consistent with Example 1. The test results were: the charge and discharge capacity in the first week reached 140.2 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 93.0%.

[0107] Example 7

[0108] This embodiment provides a method for preparing an electrode precursor material having a yolk-shell structure, and the process steps are as follows:

[0109] (1) Nickel chloride, cobalt chloride and manganese chloride are dissolved in deionized water at a molar ratio of 6:1:3 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0110] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0111] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0112] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 3:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 800°C.

[0113] (5) The obtained electrode precursor material is sintered to prepare a positive electrode for electrical performance testing. The preparation of the electrode precursor material into a lithium-ion battery and the testing method are substantially the same as those in Example 1, except that lithium carbonate is used instead of sodium carbonate in the preparation of the positive electrode, and LiPF is used in the electrolyte. 6 Replacement of NaPF 6 The test results are as follows: the charge and discharge capacity in the first week reached 190.3mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate is 97.5%.

[0114] Comparative Example 1

[0115] This comparative example provides a method for preparing an electrode precursor material, and the process steps are as follows:

[0116] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0117] (2) Add PVP at 10 g / L to the above metal salt solution and mix well.

[0118] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0119] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate is set to 3:1, the negative pressure is set to -100Pa, and the set temperature is 800℃.

[0120] (5) The electrode precursor material is obtained at the outlet of the pyrolysis furnace. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 120 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 75%.

[0121] Comparative Example 2

[0122] This comparative example provides a method for preparing an electrode precursor material, and the process steps are as follows:

[0123] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0124] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0125] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0126] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 1:2, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 800°C.

[0127] (5) The electrode precursor material is obtained at the outlet of the pyrolysis furnace. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 131 mAh g -1 , after 100 cycles at 0.1C current density, the capacity retention rate was 76%.

[0128] Comparative Example 3

[0129] This comparative example provides a method for preparing an electrode precursor material, and the process steps are as follows:

[0130] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0131] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0132] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0133] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 3:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 500°C.

[0134] (5) The electrode precursor material is obtained at the outlet of the pyrolysis furnace. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 120 mAh g -1 , after 100 cycles at 0.1C current density, the capacity retention rate was 71%.

[0135] Comparative Example 4

[0136] This comparative example provides a method for preparing an electrode precursor material, and the process steps are as follows:

[0137] (1) Nickel chloride, ferrous chloride and manganese chloride are dissolved in deionized water at a molar ratio of 1:1:1 to prepare a metal salt solution, wherein the total metal ion concentration of the prepared metal solution is 150 g / L.

[0138] (2) Add 3 g / L of PVP to the above metal salt solution and mix well.

[0139] (3) Prepare SnCl with a concentration of 0.5 mol / L 4 Solution.

[0140] (4) The metal salt solution and the tin chloride solution are sprayed into the pyrolysis furnace through two atomizing nozzles, respectively. The pyrolysis furnace is filled with an oxygen atmosphere. The metal salt solution inlet flow rate is set to be equal to the SnCl 4 The solution inlet flow rate was set at 3:1, the negative pressure was set at -100Pa, and the pyrolysis temperature of the pyrolysis furnace was set at 1100°C.

[0141] (5) The electrode precursor material is obtained at the outlet of the pyrolysis furnace. The electrode precursor material is prepared into a sodium ion battery and the test method is consistent with Example 1. The test results are: the charge and discharge capacity in the first week reaches 129.1 mAh g -1 , after 100 cycles at a current density of 0.1C, the capacity retention rate was 87%.

[0142] In summary, the scheme of the embodiment of the present invention adopts spray pyrolysis technology to prepare the yolk-shell structure oxide precursor of the positive electrode material of the sodium ion battery in one step. At the same time, the volatility of tin chloride is utilized to realize the surface coating of the metal oxide by tin chloride, which inhibits the phase change during the cycle, improves the electrochemical performance, and can also reduce the cation mixing of the positive electrode material. At the same time, it can also inhibit the undesirable side reactions at the electrolyte interface due to the high alkalinity of the surface of the active material. The material has a yolk-shell structure, and both the functional shell and the core can contact the electrolyte, ensuring a large contact area between the electrode and the electrolyte, thereby providing more active sites for sodium storage, which can significantly improve the reversible capacity. The openings distributed on the shell surface not only provide a large interface for the storage of lithium ions, but also enhance the penetration of the electrolyte, shorten the diffusion length of lithium ions, and improve the rate performance. The void space of the layered yolk-shell structure provides a buffer area for the huge volume expansion caused by the insertion / extraction of lithium ions, thereby improving the stability of the structure, thereby obtaining excellent cycle performance. In addition, Sn 2+ The incorporation of helps to inhibit phase changes during cycling, improve electrochemical performance, reduce cation mixing in the positive electrode material, and inhibit undesirable side reactions at the electrolyte interface due to the high alkalinity on the surface of the active material.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electrode precursor material, characterized in that: Its structure includes a surface shell and a metal oxide core from the outside to the inside, wherein the surface shell includes a metal oxide shell layer and a tin oxide coating layer coated on the surface of the metal oxide shell layer, wherein a hollow cavity is provided between the metal oxide shell layer and the metal oxide core, and the surface shell has a microporous structure connecting its outer surface and the hollow cavity.

2. The electrode precursor material according to claim 1, characterized in that: The metal oxide constituting the metal oxide core and the metal oxide shell are the same, and the metal element of the metal oxide is selected from at least one of Ni, Co, Mn, Cu, Mg, Mo, W, Ca, Zn, Nb, Cr, Zr, Ti and Fe; Preferably, the metal elements of the metal oxide are Ni x A y Mn 1-x-y , wherein A is selected from at least one of Co, Fe and Cu, 0.9≥x>0.5, 0.5≥y>0.

1.

3. The electrode precursor material according to claim 1 or 2, characterized in that: The metal elements of the metal oxide are Ni x Fe y Mn 1-x-y , wherein 0.9≥x>0.5, 0.5≥y>0.1; the unit cell parameters of the electrode precursor material have the following characteristics: α=β=γ=90°, in the X-ray diffraction spectrum, the ratio of the diffraction peak intensity of the (311) crystal plane to the diffraction peak intensity of the (440) crystal plane is 2.6~2.9; And / or, the particle size of the metal oxide core is 50nm to 500nm, the thickness of the metal oxide shell is 1nm to 10nm, and the thickness of the tin oxide coating layer is 0.5nm to 2nm; And / or, the micropore size of the microporous structure is 0.1nm to 20nm, and the specific surface area of ​​the battery precursor material is 4 to 10m 2 / g.

4. A method for preparing an electrode precursor material according to any one of claims 1 to 3, characterized in that: It includes: The metal salt solution and the tin chloride solution are respectively sprayed into a pyrolysis furnace through two atomizing nozzles, and pyrolyzed in an oxygen atmosphere to form the electrode precursor material, wherein a template agent is added to the metal salt solution.

5. The preparation method according to claim 4, characterized in that: The template agent is selected from at least one of polyvinyl pyrrolidone, polyamide-amine, polyacrylamide, citric acid, polyvinyl alcohol and ethylenediamine; preferably, the template agent is polyvinyl pyrrolidone.

6. The preparation method according to claim 4, characterized in that: The pyrolysis temperature is 600°C to 1000°C, preferably 700°C to 900°C; And / or, the negative pressure value of the pyrolysis furnace is -100Pa to -500Pa.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The amount of the template added to the metal salt solution is 0.5 g / L to 5 g / L, preferably 3 g / L to 5 g / L; and / or, the total metal ion concentration in the metal salt solution is 100 g / L to 250 g / L, preferably 150 g / L to 200 g / L; and / or, the concentration of the tin chloride solution is 0.1 mol / L to 2 mol / L, preferably 0.5 mol / L to 1 mol / L; And / or, the ratio of the inlet flow rate of the metal salt solution to the inlet flow rate of the stannic chloride solution is (1-5):1, preferably (2-4):

1.

8. A method for preparing a positive electrode material, characterized in that: It includes: The electrode precursor material according to any one of claims 1 to 3 is sintered with a sodium source or a lithium source.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode film layer arranged on the current collector, and the positive electrode film layer comprises the positive electrode material prepared by the preparation method according to claim 8.

10. A secondary battery, characterized in that: It includes the positive electrode sheet as claimed in claim 9.